1991
DOI: 10.1148/radiology.179.3.2027972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bone distribution on vertebral strength: assessment with patient-specific nonlinear finite element analysis.

Abstract: Three-dimensional quantitative computed tomographic (QCT) studies of the lumbar spine were extended with finite element analysis (FEA) to include bone distribution in assessment of vertebral body strength. Fifty-nine FEA models were created from data from 43 patients, 28 with no evidence of osteoporosis and 15 with previous vertebral fractures. Simulated loads were applied to the vertebral models to estimate vertebral strength. Yield strength in the models from patients with osteoporosis was 0.22-1.05 MPa (ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(124 citation statements)
references
References 0 publications
4
118
0
2
Order By: Relevance
“…A previous parametric study had indicated that the load sharing between the cortical shell and trabecular bone was insensitive to the assumed modulus of the disc [11], and therefore, the focus here was specifically on the sensitivity of our results to the assumed Poisson's ratio of the disc. Further, to simulate a common biomechanical test on isolated vertebra [13][14][15], a third set of analyses were run in which the vertebral body was loaded through a PMMA layer (Young's modulus of 2500 MPa and Poisson's ratio of 0.3 [25]) instead of a disc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous parametric study had indicated that the load sharing between the cortical shell and trabecular bone was insensitive to the assumed modulus of the disc [11], and therefore, the focus here was specifically on the sensitivity of our results to the assumed Poisson's ratio of the disc. Further, to simulate a common biomechanical test on isolated vertebra [13][14][15], a third set of analyses were run in which the vertebral body was loaded through a PMMA layer (Young's modulus of 2500 MPa and Poisson's ratio of 0.3 [25]) instead of a disc.…”
Section: Methodsmentioning
confidence: 99%
“…Our specific objectives were to: 1) determine whether the bone tissue at high risk of failure first occurs in the trabecular bone, cortical shell, or cortical endplates by quantifying the relative amount of high-risk tissue in each unit; 2) identify the anatomical location (inferior/superior) of such high-risk tissue; and 3) determine the sensitivity of these results to how the endplate is loaded, i.e. via a disc or a layer of PMMA, the latter often used in biomechanical testing of isolated vertebrae [13][14][15]. This study is the first to use such detailed analysis techniques to describe the micromechanics of initial failure at the tissue level in a cohort of elderly human vertebrae.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have speculated that DXA is an inaccurate measure of vertebral fracture risk potential because it is structurally simplistic, i.e., it reflects only volume averaged material properties, and they have focused their efforts on developing more sophisticated mechanical models of vertebral body fractures (2,8,9,14,15,19,23,36). These patient-specific models are generated from quantitative computed tomography (QCT) scans and can be classified as: 1) relatively simplistic "mechanics of solids" (MOS) models (2,8,9,14,36), such as minimum axial rigidity and stiffness, or 2) three dimensional finite element (FE) models (8,9,15,19,23). Clinical use of such techniques is still under investigation as there is no clear evidence that these methods have better outcomes than DXA-BMD in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element (FE) models derived from QCT scans are a promising alternative to BMD and MOS techniques since these models automatically incorporate bone geometry and material heterogeneity (8,15,19) and may be used to simulate various loading conditions (7)(8)(9)32). Studies have shown that QCT-based finite element predictions of vertebral strength better discriminate between osteoporotic and non-osteoporotic individuals (15) and well predict the experimental strength of lumbar vertebrae (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation